Rapid virological response of telaprevir and boceprevir in a Brazilian cohort of HCV genotype 1 patients: a multicenter longitudinal study - Borba HHL; Wiens A; Steimbach LM; Tonin FS; Pedroso MLA; Ivantes CAP; Fernandez-Llimos F; Pontarolo R (Dove Medical Press, 2017)
Helena HL Borba,1 Astrid Wiens,1 Laiza M Steimbach,1 Fernanda S Tonin,1 Maria LA Pedroso,2 Cláudia AP Ivantes,3 Fernando Fernandez-Llimos,4 Roberto Pontarolo1 1Pharmaceutical Sciences Postgraduate Research Program, Department of Pharmacy, 2Gastroenterology Service, Hospital de Clínicas, Federal University of Paraná, 3Guidance and Counseling Center, Curitiba City Hall, Curitiba, Paraná, Brazil; 4Department of Social Pharmacy, Faculty of Pharmacy, Research Institute for Medicines, University of Lisboa, Lisbon, Portugal Background: Chronic hepatitis C is a major public health issue, but there is a gap in the literature regarding the effectiveness and safety of direct-acting antiviral agents in the Brazilian population. The main aim of this study was to describe the effectiveness of boceprevir and telaprevir in patients treated at public health care institutions in Brazil.Materials and methods: A prospective longitudinal and multicenter study was conducted in five centers in the State of Paraná between September 2014 and June 2016. Data regarding effectiveness and safety were collected from medical records of patients treated with boceprevir or telaprevir. The effectiveness outcome comprised the rapid virological response (RVR). Multivariate analysis was performed to verify the influence of independent variables (ie, age, gender, baseline viral load) on RVR achievement.Results: Data were collected from 117 patients with chronic hepatitis C virus (HCV) genotype 1 infection. Fifteen patients received treatment with boceprevir and 102 received telaprevir. The mean age was 51.6 years, 64.1% were male, 44.4% were infected with HCV subtype 1a, 62.4% had a high baseline viral load (≥800,000 IU/mL) and 33% were cirrhotic. Furthermore, 79.5% of patients achieved RVR (26.7% in the boceprevir group and 87.3% in the telaprevir group). Multivariate analysis demonstrated that the type of protease inhibitor (boceprevir or telaprevir) and the baseline viral load had an influence on the RVR rate (odds ratio [OR] =0.011; 95% confidence interval [CI]: 0.001–0.119; P<0.001/OR =13.004; 95% CI: 1.522–111.115; P=0.019, respectively).Conclusion: In this longitudinal multicenter cohort study conducted from the Brazilian perspective, differences were found in the RVR rates, favoring telaprevir over boceprevir for genotype 1 HCV-infected patients. In addition, the baseline viral load was associated with RVR achievement in both evaluated groups. As RVR is also reported in the literature as a predictor of the sustained virological response (SVR), further analyses of RVR as predictor of SVR outcomes should be further evaluated in Brazil. Keywords: hepatitis C, rapid virological response, protease inhibitors, telaprevir, boceprevir, multicenter